2009
DOI: 10.1210/en.2009-0285
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Corticotropin-Releasing Hormone Receptor 2α Splice Variant Is Efficiently Translated But Not Trafficked for Secretion

Abstract: CRH directs the physiological and behavioral responses to stress. Its activity is mediated by CRH receptors (CRH-R) 1 and 2 and modulated by the CRH-binding protein. Aberrant regulation of this system has been associated with anxiety disorders and major depression, demonstrating the importance of understanding the regulation of CRH activity. An mRNA splice variant of CRH-R2alpha (sCRH-R2alpha) was recently identified that encodes the receptor's ligand-binding extracellular domain but terminates before the tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 66 publications
0
17
0
Order By: Relevance
“…The CRF 2(a) R instead possesses a pseudo signal peptide, which is unable to mediate ER targeting, remains uncleaved, and forms an additional hydrophobic domain at the N tail of the receptor, which is so far unique within the GPCR protein family (11)(12)(13)(14). Conventional signal peptide functions are blocked by a single amino acid residue (Asn 13 ), and mutation of this residue causes conversion to a cleaved signal peptide (11).…”
mentioning
confidence: 99%
“…The CRF 2(a) R instead possesses a pseudo signal peptide, which is unable to mediate ER targeting, remains uncleaved, and forms an additional hydrophobic domain at the N tail of the receptor, which is so far unique within the GPCR protein family (11)(12)(13)(14). Conventional signal peptide functions are blocked by a single amino acid residue (Asn 13 ), and mutation of this residue causes conversion to a cleaved signal peptide (11).…”
mentioning
confidence: 99%
“…The antibody that was used is likely to recognize all known isoforms of the CRF 2 receptor because the antibody recognizes a 12-amino acid sequence of the N-terminus that is nearly identical in all CRF 2 receptor isoforms that have been characterized (Figure 1). A recent study (Evans and Seasholtz, 2009) has shown that the sCRF 2α receptor is found in the rat brain, and that the mRNA is efficiently translated. In addition Evans and Seasholtz (2009) showed that the sCRF 2α receptor is not trafficked to the membrane, which may account in part for the apparent abundance of cytoplasmic staining seen in this study and previous studies (Waselus et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study (Evans and Seasholtz, 2009) has shown that the sCRF 2α receptor is found in the rat brain, and that the mRNA is efficiently translated. In addition Evans and Seasholtz (2009) showed that the sCRF 2α receptor is not trafficked to the membrane, which may account in part for the apparent abundance of cytoplasmic staining seen in this study and previous studies (Waselus et al, 2009). Consistent with these findings, recent studies by Schulz and colleagues (2010) showed that CRF 2α receptor contains an N-terminal pseudo signal peptide that is unable to target the peptide to the endoplasmic reticulum membrane, resulting in very low cell surface expression (Schulz et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations